Turraea tugelensis, a new species of Turraea sect. Nurmonia (Meliaceae) from South Africa - Crouch, Neil R.; Styles, David G.a. (Phytotaxa, 2020)
A new Turraea species, Turraea tugelensis is described from along the margins of woodland in the lower Tugela River valley in eastern KwaZulu-Natal, South Africa. This vicariant species is in Turraea sect. Nurmonia, and allied to the herbaceous suffruticose species T. pulchella and T. streyi, from which it is separable on both vegetative and sexual characteristics.